Observations of Tilted Electron Vortex Flux Rope in the Magnetic Reconnection Tailward Outflow Region - K. Jiang; S. Y. Huang; Z. G. Yuan; Q. Y. Xiong; Y. Y. Wei (Geophysical Research Letters)
Abstract With high‐resolution data from Magnetospheric Multiscale (MMS) mission, an ion‐scale flux rope (FR) with a heavily tilted axis is observed in the tailward outflow of a magnetic reconnection in the terrestrial magnetotail. Combined with the field‐aligned electron distribution and positions of MMS when the X‐line and FR are observed, the tilted axis is inferred to be caused by the extension of the X‐line in the dawn‐dusk direction. J · E′ is negative and electrons are losing energy in the FR. An ion‐scale electron vortex embedded in the plane perpendicular to the axis is observed inside FR. The induced magnetic field generated by the electron vortex has the same direction as the axial component, which can contribute to the axial component and increase the magnetic flux of the FR. Such electron vortex FRs may be an essential carrier of magnetic flux from near‐Earth X‐line to distant X‐line or interplanetary space.